Flame-Resistant Poly(vinyl alcohol) Composites with Improved Ionic Conductivity - Diana Serbezeanu; Corneliu Hamciuc; Tăchiță Vlad-Bubulac; Alina-Mirela Ipate; Gabriela Lisa; Ina Turcan; Marius Andrei Olariu; Ion Anghel; Dana Maria Preda (Membranes, 2023)
Flame-resistant polymer composites were prepared based on polyvinyl alcohol (PVA) as a polymer matrix and a polyphosphonate as flame retardant. Oxalic acid was used as crosslinking agent. LiClO4, BaTiO3, and graphene oxide were also incorporated into PVA matrix to increase the ionic conductivity. The obtained film composites were investigated by infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis, differential scanning calorimetry and microscale combustion tests. Incorporating fire retardant (PFRV), BaTiO3, and graphene oxide (GO) into a material results in increased resistance to fire when compared to the control sample. A thermogravimetric analysis revealed that, as a general trend, the presence of PFRV and BaTiO3 nanoparticles enhances the residue quantity at a temperature of 700 °C from 7.9 wt% to 23.6 wt%. Their dielectric properties were evaluated with Broad Band Dielectric Spectroscopy. The electrical conductivity of the samples was determined and discussed in relation to the LiClO4 content. The electrical properties, including permittivity and conductivity, are being enhanced by the use of LiClO4. Additionally, a relaxation peak has been observed in the dielectric losses at frequencies exceeding 103 Hz. The electrical properties, including permittivity and conductivity, are being enhanced by the use of LiClO4. Additionally, a relaxation peak has been observed in the dielectric losses at frequencies exceeding 103 Hz. Out of the various composites tested, the composite containing 35 wt% of LiClO4 exhibits the highest alternating current (AC) conductivity, with a measured value of 2.46 × 10−3 S/m. Taking into consideration all the aspects discussed, these improved composites are intended for utilization in the manufacturing of Li-Ion batteries.